2020
DOI: 10.1007/s11357-020-00227-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of parental longevity with the aging brain—results from UK Biobank

Abstract: A few studies report that parental longevity is associated with preserved cognition and physical function and lower risk of Alzheimer's disease. However, data on structural neuroimaging correlates of parental longevity and its spatial distribution are limited. This study aims to examine relationships of parental longevity with regional brain structure and to explore sex differences. We identified 12,970 UK Biobank participants (mean age=64.4, 51.5%women) with data on parental longevity, regional gray matter vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…Our finding of a lack of association of the longevity measures with cortical and grey matter volumes is also consistent with the aforementioned study that examined the association with parental longevity (⩾85 yrs) (Murabito et al, 2014). However, in another study also using UK Biobank data (Tian et al, 2020), parental longevity was associated with some brain structures, including hippocampal volumes, which we did not find in the present study. The Tian et al study again defined parental longevity differently using age 85 as the cut-off, unlike our examination in relation to parental lifespan beyond 40 years, which we analysed as a continuous trait.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our finding of a lack of association of the longevity measures with cortical and grey matter volumes is also consistent with the aforementioned study that examined the association with parental longevity (⩾85 yrs) (Murabito et al, 2014). However, in another study also using UK Biobank data (Tian et al, 2020), parental longevity was associated with some brain structures, including hippocampal volumes, which we did not find in the present study. The Tian et al study again defined parental longevity differently using age 85 as the cut-off, unlike our examination in relation to parental lifespan beyond 40 years, which we analysed as a continuous trait.…”
Section: Discussioncontrasting
confidence: 99%
“…Observational studies have shown that individuals with long-lived parents have less cognitive impairment (Andersen et al, 2019; Dutta et al, 2014), lower risk of Alzheimer’s disease (Lipton et al, 2010), healthier brain ageing processes (Murabito et al, 2014), and better-preserved brain structure (Tian et al, 2020). Furthermore, it has been shown that age-related brain changes occur over the adult lifespan, with GM and white matter (WM) atrophy (Driscoll et al, 2009; Fjell et al, 2009; Pfefferbaum et al, 2013; Raz et al, 2010; Storsve et al, 2014) and the accumulation of WMH (Wen and Sachdev, 2004; Wen et al, 2009), which are also features of neurodegeneration and cerebrovascular burden.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain is a complex experience that involves sensory-discriminative, affective-motivational, and cognitive-evaluative dimensions. When investigating the relationships of parental longevity with the regional brain structure, some differences in zones involved in transferring and processing sensory and nociceptive information, which might support our results, have been found, but more research is needed on this issue [ 53 ].…”
Section: Discussionmentioning
confidence: 56%
“…In total, 19 IDPs were involved, including volume of grey matter (GM), the volume of white matter (WM), volume of brain (GM+WM), regional grey matter volumes (i.e., volumes of GM in superior frontal gyrus, inferior frontal gyrus, middle frontal gyrus, supplementary motor cortex, precentral gyrus, postcentral gyrus, precuneus, superior parietal lobe, parahippocampal gyrus, middle temporal gyrus, and inferior temporal gyrus), and volumes of several subcortical areas (including hippocampus, putamen, thalamus, caudate, and amygdala). Especially, volumes of grey matter, white matter, and the total brain were normalized by head size 32 . For the other IDPs, the sum of volumes in the left and right hemispheres was calculated.…”
Section: Methodsmentioning
confidence: 99%